Romanticizing the Monster: A Postmodern Study of L.J. Smith’s The Vampire Diaries - Imdad, Jonathan Caleb (Linguistics and Literature Review, 2025)
This research explores the influence and impact of postmodernism on the transformation of monstrous archetypes in contemporary literature by focusing on L.J. Smith’s The Vampire Diaries. The study primarily examines the romanticization and humanization of vampires and how monsters in the postmodern age no longer serve as evil antagonists. In the present research, a qualitative and explorative research design is used through a postmodern lens to argue that the concept of monstrosity embraces subjectivity and ambiguity in the modern world. Jean Francois Lyotard’s description of the postmodern condition as a sense of skepticism toward dominant metanarratives is central to this shift, as it challenges classical binaries and dismantles rigid societal norms. This disposition of fluidity and relativity of meaning is exemplified in The Vampire Diaries through the portrayal of vampires as normal human beings as Smith strikes a delicate balance between their gruesome nature and the complexity of their character. The research draws on the concepts of identity, power, and morality to argue that these notions are subjective and even creatures like vampires are capable of love and care. This cultural shift suggests society’s increasing embrace of diversity and complex interpretations of identity in the postmodern age. L.J. Smith’s work demonstrates how literary and cultural landscapes have evolved, resisting absolutism and celebrating multiplicity.